REDESCRIPTION OF TWO MILKWEED BUTTERFLIES OF GENUS DANAUS, KULK - B. Mal; N. Memon; M. A. Shah; S. A. Memon; N. A. Shah (Journal of Animal and Plant Sciences, 2015)
Two species of genus Danaus Kluk (1802), Danaus chrysippus Linnaeus (1758) and Danaus genutia Cramer (1779), commonly called monarchs, queens and milkweed butterflies are re-described. This re-description is based on coloration of wings, structure of mouthparts, maxillary palpi and internal male and female genitalia. The occurrence of these species of butterflies is new record from Jamshoro, Sindh, Pakistan.
Keywords: Re-description; Butterflies; Danaus KULK; Jamshoro; Sindh